2019
DOI: 10.1590/1981-6723.19718
|View full text |Cite
|
Sign up to set email alerts
|

Yeasts isolated from tropical fruit ice creams: diversity, antifungal susceptibility and adherence to buccal epithelial cells

Abstract: Fruit-based ice creams are products widely consumed in tropical countries and, because of their composition, can be a good source for microbial growth, including opportunistic pathogens. The aims of this study were to characterize the yeast populations present in Brazilian fruit-based ice creams, and to investigate the antifungal susceptibility to amphotericin B, fluconazole and itraconazole, and the ability of the isolates that were able to grow at 37 ºC to adhere to buccal epithelial cells (BEC). Two hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…These species formerly belonged to the genus Cryptococcus, but after a recent reclassification they were assigned to the mentioned genera [55]. In accordance with this study, a few incidences of C. curvatus have been reported in the air of dairy environments [56], whereas P. flavescens has rarely been identified in dairy matrices such as ice cream and cheese brine [38,45]. The presence of C. moniliiforme is undesirable in white-brined cheese, as it is able to form melanin-like brown pigments, leading to product discoloration [57].…”
Section: Diversity Of Yeasts In Cheese Productionsupporting
confidence: 79%
See 1 more Smart Citation
“…These species formerly belonged to the genus Cryptococcus, but after a recent reclassification they were assigned to the mentioned genera [55]. In accordance with this study, a few incidences of C. curvatus have been reported in the air of dairy environments [56], whereas P. flavescens has rarely been identified in dairy matrices such as ice cream and cheese brine [38,45]. The presence of C. moniliiforme is undesirable in white-brined cheese, as it is able to form melanin-like brown pigments, leading to product discoloration [57].…”
Section: Diversity Of Yeasts In Cheese Productionsupporting
confidence: 79%
“…It is a common spoilage organism in various types of cheeses (brined, ripened, Swiss-type, blue-veined), characterized by high proteolytic and lipolytic activities [7,11,43]. Similar to C. auris, C. parapsilosis is considered as an opportunistic human pathogen causing invasive candidiasis [11,44,45]. At the same time, C. parapsilosis is regularly encountered in other fermented products, having positive impact on their organoleptic properties.…”
Section: Diversity Of Yeasts In Cheese Productionmentioning
confidence: 99%
“…Our analysis revealed that these Candida yeasts were found in fermented fish samples from two provinces (20%). However, some of yeast strains, such as C. tropicalis , C. glabrata , C. intermedia , and C. parapsilosis , have been reported as spoilage yeasts and opportunistic human pathogens [ 58 , 59 , 60 , 61 , 62 ]. They may present as a result of unsanitary manufacturing processes.…”
Section: Resultsmentioning
confidence: 99%
“…They may present as a result of unsanitary manufacturing processes. Moreover, the use of raw fish without thermal treatment contributes to the presence of pathogens in the final product [ 58 , 59 , 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…isolates appeared to be phylogenetically related to F. circinatum. Recently,Lima et al (2019) found that in tropical fruit-based ice creams (including pineapple based) the predominant species were Candida intermedia, Torulaspora delbrueckii, Candida parapsilosis, Clavispora lusitaniae, Saccharomyces cerevisiae and Pichia kudriavzevii.…”
mentioning
confidence: 99%